Diabetes care and prevention services provided by pharmacists: Progress made during the COVID-19 pandemic and the need for additional efforts in the post-pandemic era - Mohamed Hassan Elnaem; Wesley Nuffer (Elsevier, 2022)
Diabetes is a challenging metabolic disease that significantly impacts people's health worldwide. It requires a comprehensive approach for better prevention and control, especially during challenging times such as the recent pandemic. The COVID-19 pandemic has altered how health care professionals, including pharmacists, provide health care. With the widespread use of virtual and online platforms for service delivery, pharmacist-led diabetes care has been transformed to meet the needs of patients during the pandemic. This article aims to discuss examples of pharmacist-led diabetes care services during the pandemic and highlight areas where additional pharmacist efforts are needed in the post-pandemic era.